BovDB: a data set of stock prices of all companies in B3 from 1995 to 2020 - Corrêa Cardoso, Fabian; Valverde Malska, Juan Andrey; Ramiro, Paulo Junior; Lucca, Giancarlo; Nunes Borges, Eduardo; Leite Dias de Mattos, Viviane; Alceste Berri, Rafael (Journal of Information and Data Management, 2022)
Stock markets are responsible for the movement of vast amounts of financial resources worldwide. This market generates a high volume of transaction data, which after being analyzed are very useful for many applications. In this article, we present BovDB, a data set that was built considering a source of the Brazilian Stock Exchange (B3) with information related to the years between 1995 and 2020. We have approached the events’ impact on the stocks by applying a cumulative factor to correct prices. The results were compared with public data from InfoMoney and BR Investing, showing that our methods, are valid and follow the market standards, based on the proposed factor. BovDB data set can be used as a benchmark for different applications and it is available in open access for any researcher on GitHub.